Answer:
The solution is -24, the first choice.
Explanation:
The given equation is
![(2)/(3)((1)/(2)x+12 )=(1)/(2)((1)/(3)x+14 ) -3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ant2o4ft2qqsyr2i2bjofhoyjibhmam79e.png)
First, we use distributive property
![(2)/(6)x+(24)/(3)=(1)/(6)x+(14)/(2)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/66tcjz4mftxoieefrh73g8szkny336dy5m.png)
Then, we simplify fractions
![(1)/(3)x+8=(1)/(6)x+7-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/oslu1e8uvkztd5bp55g3g5cj65zish15yu.png)
Now, we move all variables to the left and all constants to the right, and solve for
![x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p9sq9b3rc5nwoqzhzc8wcaj51b36281l9g.png)
![(1)/(3)x-(1)/(6)x=4-8\\(6-3)/(18)x=-4\\ (3)/(18)x=-4\\(1)/(6)x=-4\\ x=-24](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cey7t6lc43pohq5ajpq99dsl2wcwqss0r1.png)
Therefore, the solution is -24, the first choice.